2017
DOI: 10.3389/fmicb.2017.02512
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Phylogenetic Group Patterns of Escherichia coli from Commensal Human and Wastewater Treatment Plant Isolates

Abstract: Escherichia coli is an important microorganism in the gastrointestinal tract of warm-blooded animals. Commensal populations of E. coli consist of stable genetic isolates, which means that each individual has only one phylogenetic group (phylogroup). We evaluated the frequency of human commensal E. coli phylogroups from 116 people and observed that the majority of isolates belonged to group A. We also evaluated the frequency of phylogroups in wastewater samples and found a strong positive correlation between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
52
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 91 publications
20
52
2
Order By: Relevance
“…For the rest, the analysis showed a good correspondence between the assignment into the known phylogroups - A, B1, B2, D, E, F, and G – and the different clades of this tree. In line with the literature 40 , four major phylogroups were very abundant - A (24% of the dataset), B1 (24%), B2 (25%) and D (14%) – whereas the others were rarer. The nucleotide diversity of the phylogroups is very dependent on their phylogenetic structure, since some clades have more closely related clusters of strains than others (Supplementary Fig.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…For the rest, the analysis showed a good correspondence between the assignment into the known phylogroups - A, B1, B2, D, E, F, and G – and the different clades of this tree. In line with the literature 40 , four major phylogroups were very abundant - A (24% of the dataset), B1 (24%), B2 (25%) and D (14%) – whereas the others were rarer. The nucleotide diversity of the phylogroups is very dependent on their phylogenetic structure, since some clades have more closely related clusters of strains than others (Supplementary Fig.…”
Section: Resultssupporting
confidence: 88%
“…This allowed us to study the joint effect of population structure and habitat on the variation of gene repertoires. Our study focused on E. coli isolates from Australia, but its genetic diversity was higher or comparable to other worldwide genome datasets, and its population structure was consistent with previous works 16, 40, 74 . This indicates that what we have observed is likely to be representative of the species as a whole.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There is a possibility, however, that some of our observations may reflect high mortality rates of certain E. coli clones. We found that all isolates belonged to phylogroups B2 and D, which have been found previously in domestic animals and the environment (Stoppe et al., ); however, the B2 phylogroup is not common in environments outside of the host, and neither B2 nor D phylogroups have been found to be common in poultry (Blyton et al., ).…”
Section: Discussionsupporting
confidence: 75%
“…Bacteria are paragons of adaptability and make up more biomass than all organisms other than plants 28 combined (Bar-On, Phillips, and Milo 2018). Many bacterial species have enormous population sizes, 29 disperse effectively around the globe (Stoppe et al 2017) and exhibit high rates of within-species 30 homologous recombination (Vos and Didelot 2009). Recombination acts to progressively break down 31 non-random associations between markers (linkage disequilibrium), so that in large populations a 32 natural null expectation is for there to be linkage equilibrium between sites.…”
Section: Introduction 27mentioning
confidence: 99%